(untitled) (Eurasian Medical Research Periodical, 2023)
The article provides information on the importance of vitamins used in the treatment of varicose veins, and the determination of the amount of water-soluble vitamins in an aqueous extract of chestnut fruits using the "High-Performance Liquid Chromatography" method.